The Science Communication Challenge Truth and Disagreement in Democratic Knowledge Societies - Meyer, Gitte (Anthem Press, 2018)
The Science Communication Challenge explores and discusses the whys - as distinct from the hows - of science communication. Arguing that the dominant science communication paradigm is didactic, it makes the case for a political category of science communication, aimed at furthering discussions of science-related public affairs and making room for civilized and reasonable exchanges between different points of view. As civil societies and knowledge societies, modern democratic societies are confronted with the challenge of accommodating both the scientific logic of truth-seeking and the classical political logic of pluralism. The didactic science communication paradigm, however, is unsuited to dealing with substantial disagreement. Therefore, it is also unsuited to facilitate communication about the steadily increasing number of science-related political issues. Using insights from an array of academic fields, The Science Communication Challenge explores the possible origins of the didactic paradigm, connecting it to particular understandings of knowledge, politics and the public and to the widespread assumption of a science-versus-politics dichotomy. The book offers a critique of that assumption and suggests that science and politics be seen as substantially different activities, suited to dealing with different kinds of questions - and to different varieties of science communication.